2020
DOI: 10.1186/s12889-019-8115-0
|View full text |Cite
|
Sign up to set email alerts
|

Violence against children and intimate partner violence against women: overlap and common contributing factors among caregiver-adolescent dyads

Abstract: Background: Intimate partner violence against women (IPV) and violence against children (VAC) are both global epidemics with long-term health consequences. The vast majority of research to date focuses on either IPV or VAC, however the intersections between these types of violence are a growing area of global attention. A significant need exists for empirical research on the overlap of IPV and VAC, especially in contexts with particularly high rates of both types of violence. Methods: This exploratory study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 60 publications
5
25
0
5
Order By: Relevance
“…20 The second study, including around 300 Ugandan adolescents, found that overlapping IPV and CM was associated with lower caregiver education and SES (socioeconomic status), lower partner attachment and higher mental distress and alcohol use among female caregivers and lower partner attachment as well as attitudes favouring violence against children among male caregivers. 22 No studies of risk factors for IPV and CM among young children were found. The current study empirically confirms, in a large population-based birth cohort, the theoretical proposition, derived principally from two parallel literatures, that IPV and CM share many risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The second study, including around 300 Ugandan adolescents, found that overlapping IPV and CM was associated with lower caregiver education and SES (socioeconomic status), lower partner attachment and higher mental distress and alcohol use among female caregivers and lower partner attachment as well as attitudes favouring violence against children among male caregivers. 22 No studies of risk factors for IPV and CM among young children were found. The current study empirically confirms, in a large population-based birth cohort, the theoretical proposition, derived principally from two parallel literatures, that IPV and CM share many risk factors.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Participants reporting only IPV or only CM had many similar characteristics, but co-occurrence was particularly likely in the context of non-violent marital conflict and parental drug use. Two school surveys of Ugandan adolescents 20 22 found substantial overlap between IPV and CM (present for about one quarter to one-third of the adolescents), and one survey 22 showed this co-occurrence was associated with lower caregiver education, less emotional attachment in the partner relationship and higher caregiver mental distress and alcohol use. In short, there are very few recent representative studies of the overlap between IPV and CM and possible shared risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…La violencia de género ha sido reconocida como una violación de los derechos humanos y un problema global de salud pública (World Health Organization [WHO], 2016) con secuelas, especialmente psicológicas, tanto en las mujeres maltratadas (Rosser et al, 2020;Vilariño et al, 2018) como en los/as hijos/as como víctimas directas e indirectas (Carlson et al, 2020;WHO, 2016), si bien estos han sido frecuentemente invisibilizados como víctimas (Fantuzzo et al, 2000;Novo et al, 2016). La literatura revela que la exposición a la violencia de género produce en los hijos e hijas consecuencias físicas, psicoemocionales, conductuales y escolares (Alisic et al, 2015;Carracedo et al, 2018;Seijo et al, 2009;Seijo et al, 2016).…”
Section: Introductionunclassified
“…Considerada como um grave problema de saúde pública, tanto pela Organização Mundial de Saúde (OMS) quanto pelo Ministério da Saúde brasileiro, a violência vem tomando proporções globais assustadoras nas últimas décadas, sobretudo aquelas ocorridas no seio familiar, vitimando crianças e adolescentes naquele espaço que por pressuposição deveria garantir segurança, proteção e apoio para o crescimento e desenvolvimento infantil adequados 1,2 .…”
Section: Introductionunclassified
“…direitos básicos -como moradia, transporte e educação, expressividade esta que culminou na institucionalização da questão urbana, viabilizada pelo Estatuto da Cidade em 20011 . Em Marituba, no entanto, a precarização das condições de vida vai além da Nacional de Meio Ambiente, estabelecida pela Lei nº 6.938, de 31 de agosto de 1981, que tem como objetivo a preservação, melhoria e recuperação da qualidade ambiental propícia à vida humana.…”
unclassified